Application of Artificial Intelligence in Legal Research and Court Practice (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the application of artificial intelligence (AI) technologies in legal research and judicial practice. SI plays an important role in the legal field in automating legal documents, predicting court decisions and resolving disputes. These technologies play an important role in speeding up legal processes, increasing efficiency and reducing human errors. However, challenges related to the application of SI, including legal regulation, privacy and security issues, are also highlighted.